Community participatory interventions to improve farmer knowledge and practices of household biogas unit operation in Ha Nam Province, Vietnam - Luu Quoc Toan; Mai Huong Nguyen; Hung Nguyen-Viet; Giang Pham; Tung Dinh-Xuan; MacDonald, L.E.; Phuc Pham Duc (Ovid Technologies, 2018)
Context: The use of biogas systems to treat livestock waste is a common practice in Vietnam. However, farmers' knowledge and practices of the safe and appropriate use of household biogas units (HBUs) are still limited and could negatively impact human, animal, and environmental health. Objective: To assess the effectiveness of an intervention to improve knowledge and practices of biogas operation among farmers in 2 communes of Ha Nam Province, Vietnam. Design: A community-based intervention approach. Setting: This study was conducted from 2015 to 2016 in 2 communes of Ha Nam Province, Vietnam. Participants: Only farmers with HBUs (N = 399) participated in this research. Farmers were assigned to either an intervention group or a control group at a ratio of 1:2. Intervention: Two intervention steps were implemented over a 6-month period as follows: (i) the core farmer group trained in 6 steps of HBU safe handling practice; and (ii) the core farmer group conducted peer-to-peer communication with its neighbors in the commune using the provided material. Main Outcome Measure(s): Farmers' knowledge and practices in biogas operation were assessed by a structured questionnaire. The questionnaire was administered before (baseline) and after the intervention (follow-up) to both the control and intervention groups. Results: There was a significant difference in the knowledge and practices of biogas operation between the 2 groups, in which farmers in the intervention group demonstrated better understanding of the related topic than the control group (P < .05, t test). A linear regression model indicated that baseline and follow-up scores in both knowledge and practices of the intervention group were higher than those of the control group. After the intervention, the mean difference score in knowledge and practices between the intervention and control groups was 5.0 and 2.0 points, respectively (P < .01). Conclusion: A community-based intervention approach could be applied to improve knowledge and practices among farmers in using biogas systems. However, further studies should be conducted to assess the sustainability and effectiveness of this model.